Pelatihan Pembuatan Minuman Herbal Modern dalam Kemasan Siap Minum di Puskesmas Mojolangu: Training on Making Modern Herbal Drinks in Packaging Ready to Drink at the Mojolangu Health Center - Anggraeni, Amaliyah Dina; Utami, Kurnia Putri; Yuliadarwati, Nungki Marlian (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Training on making new herbal drinks in containers has been carried out at the Mojolangu Health Center, Malang city. The aim of the training on making new herbal drinks is to provide skills to partners in order to help improve the family economy through the creative economy. So the products produced can be marketed in public facilities such as schools and food stalls and grocery stores. The output of the training activities is to provide solutions to problems faced by the community in partner villages in an integrated manner to increase the economic value of the local community. Besides that, there is a noble value to be conveyed by the author, namely that herbal medicine is better known globally by not reducing its usefulness. Training on making new herbal drinks can be used as product ingredients/industrial development by partners as entrepreneurs. Issuance of certificates given to residents who took part in training as a form of appreciation, they have participated in training in making new herbal drinks, increased knowledge, skills, and confidence of health center cadres in the field of traditional medicine in tackling health in the community quickly and accurately. These community service activities will include experiences that are not only useful for the partner community but also the immediate family and the surrounding environment.